2012
DOI: 10.1093/rheumatology/ker425
|View full text |Cite
|
Sign up to set email alerts
|

The provisional ACR/EULAR definition of remission in RA: a comment on the patient global assessment criterion

Abstract: Frequently, patients did not meet the PGA criterion despite a good clinical disease state. Apparently the PGA is not solely influenced by RA disease activity. In patients with marked divergence between the PGA and objective clinical measurements, caution should be taken when applying the provisional ACR/EULAR definition of remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 15 publications
(12 reference statements)
3
52
0
Order By: Relevance
“…Also with data from very early RA (median disease duration 14 weeks), Vermeer et al 6 reported recently that 20.1% reached ACR/EULAR Boolean remission at 6 months when a 28-joint count was applied. In a further 21%, all criteria were fulfilled except for the PtGA≤1.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also with data from very early RA (median disease duration 14 weeks), Vermeer et al 6 reported recently that 20.1% reached ACR/EULAR Boolean remission at 6 months when a 28-joint count was applied. In a further 21%, all criteria were fulfilled except for the PtGA≤1.…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, it has been shown in observational studies that the major reason for not achieving remission according to the Boolean definition was PtGA>1 3–5. Moreover, these studies showed that PtGA was influenced by RA disease activity and by non-inflammatory factors—for example, fatigue, functional limitations or low back pain 3 6. Interestingly, in the BEST study7 no difference in Health Assessment Questionnaire (HAQ) scores between patients with early RA in SDAI or 28-joint count Disease Activity Score (DAS28) remission was found.…”
Section: Introductionmentioning
confidence: 99%
“…The Boolean-based definition of the provisional ACR/EULAR definition of remission in RA required a TJC28 Յ1, SJC28 Յ1, CRP level Յ1 mg/dl, and patient global assessment (PGA) Յ1 (on a 0 -10 scale) (20). In a previous study, we demonstrated that many patients did not meet the PGA criterion despite a good clinical disease state (21). Therefore, we also assessed the provisional ACR/EULAR definition of remission without the PGA criterion.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Nevertheless, it is recommended that these joints are also included in the examination. Another challenging factor is the patient global assessment, which can be influenced by joint damage and high levels of non-inflammatory symptoms [40,44,45]. This can misclassify a patient as not being in remission due to an unrelated cause and lead to overtreatment.…”
Section: Other Clinical Definitionsmentioning
confidence: 99%